A porous molecular layer modified zinc negative electrode with multiple hydrogen bond topological anchoring and a preparation method and application thereof

CN123017849APending Publication Date: 2026-10-30NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611053231.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

同时,锌离子在界面处传输不均、去溶剂化能垒较高以及局部成核差异,容易导致锌沉积不均匀和枝晶生长

Benefits of technology

第一,本发明通过酸性有机小分子单体与脒基有机小分子单体之间的质子共享和盐化作用构筑电荷辅助加强的多重氢键连接,提高多孔网络结构的稳定性和方向性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017849A_ABST
    Figure CN123017849A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of aqueous zinc ion batteries and zinc metal negative electrode surface modification, and discloses a porous molecular layer modified zinc negative electrode with multiple hydrogen bond topological anchoring as well as a preparation method and application thereof.The method takes acid group-containing organic small molecule monomers containing sulfonic acid groups or carboxylic acid groups and organic small molecule monomers containing amidine groups as raw materials, forms porous network materials with anion and cation characteristics through acid-base neutralization salting caused by proton sharing, and configures the obtained materials into a reaction solution to soak and modify polished zinc sheets.The obtained porous molecular layer has directional channels, zincophilic sites and anchoring effects of multiple hydrogen bonds, can promote zinc ion transmission and desolvation, reduces the reactivity of water molecules, thereby improving the deposition / stripping stability of the zinc negative electrode and inhibiting hydrogen evolution, corrosion and dendrite growth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aqueous zinc-ion batteries and zinc metal anode surface modification technology, specifically to a zinc anode modified with a porous molecular layer topologically anchored by multiple hydrogen bonds, its preparation method and application. Background Technology

[0002] Aqueous zinc-ion batteries have attracted widespread attention in the energy storage field due to their advantages such as high safety, relatively low raw material costs, mild preparation conditions, and suitability for large-scale energy storage. Zinc metal anodes possess good air stability and compatibility with aqueous electrolytes, making them an important anode system in aqueous zinc-ion batteries.

[0003] However, in pure water or simple zinc salt electrolytes, zinc ions typically exist in a hexahydrated form. In this solvated structure, zinc ions are coordinated with six water molecules, with oxygen atoms in the water molecules donating lone pairs of electrons to form coordinate bonds with the zinc ions. While this structure facilitates the dissolution and migration of zinc salts in water, it also makes it easier for water molecules to be transported to the zinc anode interface along with zinc ions. At the zinc anode interface, the enrichment of active water molecules easily induces water splitting and hydrogen evolution side reactions, further triggering corrosion of the zinc metal surface. Simultaneously, uneven zinc ion transport at the interface, a high desolvation energy barrier, and local nucleation differences easily lead to uneven zinc deposition and dendrite growth. These problems reduce the coulombic efficiency of zinc deposition / stripping and shorten the cycle life of zinc batteries.

[0004] Therefore, modifying the zinc anode interface to regulate the transport behavior of zinc ions at the bulk phase and interface, while simultaneously reducing the reactivity of water molecules, is an important direction for improving the stability of zinc metal anodes. Existing surface modification strategies still need to balance multiple requirements, including rapid ion transport, uniform zinc ion nucleation, zinc affinity at the interface, and inhibition of water molecule activity. Summary of the Invention

[0005] The purpose of this invention is to provide a zinc anode modified with a porous molecular layer topologically anchored by multiple hydrogen bonds and its preparation method. The aim is to improve the deposition / stripping stability of the zinc anode by regulating the interfacial transport of zinc ions, promoting the desolvation of zinc ions, and reducing the reactivity of interfacial water molecules through a porous molecular layer with directional channels and multiple hydrogen bonds.

[0006] To achieve the above objectives, this invention provides a method for preparing a zinc anode modified with a porous molecular layer and topologically anchored by multiple hydrogen bonds. The method includes: using a monomer containing a sulfonic acid group or a monomer containing a carboxylic acid group as an acidic organic small molecule monomer, and using a monomer containing an amidine group as an amidine organic small molecule monomer; forming a porous topological network material with anionic and cation-like characteristics through acid-base neutralization and salting-out caused by proton sharing between acidic groups and amidine groups in a certain molar ratio; subsequently, configuring the obtained porous network material as a reaction solution, and immersing a polished zinc sheet in it to form a zinc anode modified with a porous molecular layer and topologically anchored by multiple hydrogen bonds.

[0007] The method for preparing the zinc negative electrode provided by this invention specifically includes the following steps: S1. Under stirring, the amidoyl monomer solution containing amidoyl organic small molecule monomers is added dropwise to the acid monomer solution containing acid group organic small molecule monomers. After static reaction, a porous network material is obtained. Then, after filtration, washing and drying, a solid powder product is obtained. S2. The solid powder product is prepared as a reaction solution, and the surface-polished zinc sheet is immersed in the reaction solution. After cleaning and drying, a zinc anode modified with a porous molecular layer with multiple hydrogen bond topological anchoring is obtained. Wherein: the acidic organic small molecule monomer is selected from one of the following structures: The amidoyl organic small molecule monomer is selected from one of the following structures: ; When the acidic organic small molecule monomer is selected from one of the following structures: The amidoyl organic small molecule monomer is selected from one of the following structures: .

[0008] As a further preferred embodiment of the present invention, the solvent used for the amidine monomer solution and the acid monomer solution is a mixed solution of tetrahydrofuran and water, which is obtained by mixing water and tetrahydrofuran at a volume ratio of 0.1 to 0.6:1.

[0009] As a further preferred embodiment of the present invention, the molar ratio of the sulfonic acid group organic small molecule monomer to the amidoyl organic small molecule monomer is 2:3 to 2:6; and / or, the molar ratio of the carboxylic acid group organic small molecule monomer to the amidoyl organic small molecule monomer is 3:2 to 4:2.

[0010] As a further preferred embodiment of the present invention, the standing reaction time is 3 to 9 days; and / or, in the washing and drying steps, the solid product obtained by filtration is washed with tetrahydrofuran and dried in a vacuum drying oven at 50 to 60 ℃.

[0011] As a further preferred embodiment of the present invention, the solid powder product is uniformly dissolved in ethanol to prepare a concentration of 2-8 mg / mL. -1 The reaction solution; and / or, the zinc sheet is immersed in the reaction solution for 30 min to 2 h.

[0012] According to a second aspect of the present invention, the present invention also provides a zinc anode prepared by the preparation method described in the first aspect.

[0013] According to a third aspect of the invention, the invention also provides the application of the zinc anode of the second aspect in an aqueous zinc-ion battery.

[0014] According to a fourth aspect of the present invention, the present invention also provides a zinc-ion battery comprising a zinc negative electrode and an aqueous zinc salt electrolyte as described in the second aspect.

[0015] As a further preferred embodiment of the present invention, the zinc salt concentration in the aqueous zinc salt electrolyte is 0.5~5 mol / L. -1 .

[0016] As a further preferred embodiment of the present invention, the zinc salt is selected from at least one of zinc sulfate, zinc trifluoromethanesulfonate, zinc bis(trifluoromethanesulfonate)imide, zinc perchlorate, zinc chloride, zinc nitrate, zinc acetate, zinc fluoride, zinc hexafluoroate, zinc tetrafluoroborate, and zinc gluconate.

[0017] The principle of this invention is as follows: porous molecular layers are synthesized from small organic molecules containing carboxylic acid groups or sulfonic acid groups and small organic molecules containing amidine groups through acid-base neutralization and salting-out processes, forming a continuous topological network structure with stable connections. For example... Figure 1 As shown, this structure features hollow structures and directional channels, which can promote the rapid transport of zinc ions to the negative electrode interface and reduce the concentration gradient of zinc ions at the negative electrode interface. Simultaneously, carboxylic acid or sulfonic acid groups can provide zinc-loving sites, promoting the desolvation process of zinc ions at the negative electrode interface and improving reaction kinetics; multiple hydrogen bond interactions can effectively constrain water molecules, weakening their reactivity, thereby inhibiting hydrogen evolution, corrosion, and dendrite growth caused by uneven deposition on the zinc negative electrode surface.

[0018] Compared with the prior art, the present invention can achieve the following beneficial effects: First, this invention constructs charge-assisted enhanced multiple hydrogen bond connections through proton sharing and salting between acidic organic small molecule monomers and amidine-based organic small molecule monomers, thereby improving the stability and directionality of the porous network structure. Second, the porous molecular layer of the present invention provides zinc-loving sites and fast transport channels, which is beneficial to the uniform transport and desolvation of zinc ions. Third, the modification layer of the zinc anode can reduce the reactivity of water molecules, inhibit side reactions and dendrite growth, thereby improving the deposition / stripping reversibility of the zinc anode. Attached Figure Description

[0019] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.

[0020] Figure 1 This is a schematic diagram of a continuous topological network structure with stable connections formed on a zinc sheet according to the present invention.

[0021] Figure 2 This is a schematic diagram illustrating the mechanism of the proton-shared salt-like charge-enhanced interconnected porous topology network in this invention.

[0022] Figure 3 The image shows the XRD pattern of the topologically porous molecular material synthesized in Example 1.

[0023] Figure 4 The graphs show the zinc deposition potential test results for Example 3 and Comparative Example 1.

[0024] Figure 5 The graphs show the coulombic efficiency test results of zinc anode electrode deposition in Example 3 and Comparative Example 1.

[0025] Figure 6 The graphs show the cycle performance test results of zinc symmetric cells assembled in Example 3 and Comparative Example 1.

[0026] Figure 7 Optical photographs of the zinc anodes of Example 3 and Comparative Example 1 after cycling.

[0027] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0028] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0029] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art to which this invention pertains. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.

[0030] Example 1 This embodiment provides a zinc anode material modified with a porous molecular layer and topologically anchored by multiple hydrogen bonds, the preparation method of which includes: Step S1: Preparation of solid powder product: (1) Dissolve 2.0 mmol of sulfonic acid monomer in a mixed solution of tetrahydrofuran and water, and stir continuously at room temperature for 30 min to obtain a uniform sulfonic acid monomer solution A; wherein the mixed solution is obtained by mixing water and tetrahydrofuran at a volume ratio of 0.3:1.

[0031] The structure of the sulfonic acid monomer is as follows: .

[0032] (2) 3.0 mmol of amidine monomer was placed in a mixed solution of tetrahydrofuran and water and stirred continuously at room temperature for 30 min to obtain a homogeneous amidine monomer solution B; wherein the mixed solution was obtained by mixing water and tetrahydrofuran at a volume ratio of 0.3:1.

[0033] The structure of the amidoyl monomer is as follows: .

[0034] (3) Under continuous stirring at room temperature, the amidoyl monomer solution B is slowly added dropwise to the sulfonic acid monomer solution A, and the resulting reaction system is allowed to stand for 7 days.

[0035] (4) The reaction system was slowly filtered at room temperature, and the solid product on the filter paper was washed with tetrahydrofuran. Finally, it was dried in a vacuum drying oven at 60 °C to collect the solid powder product.

[0036] Step S2, zinc sheet surface finishing: Dissolve 5 mg of solid powder uniformly in 1 mL of ethanol to prepare 5 mg mL of the solution. -1 The zinc sheet with a polished surface is immersed in the reaction solution and left to stand for 30 minutes. The zinc sheet is then removed, cleaned, and dried to obtain a zinc anode material modified with a porous molecular layer topologically anchored by multiple hydrogen bonds.

[0037] Example 2 The difference from Example 1 is that only the amidine monomer is replaced, while the other conditions are the same as in Example 1.

[0038] The structure of the amidine monomer used is as follows: .

[0039] Example 3 The difference from Example 2 is that the only difference is that the soaking time of the zinc sheet in the reaction solution is changed to 1 hour, while the other conditions are the same as in Example 2.

[0040] Example 4 The difference from Example 2 is that the soaking time of the zinc sheet in the reaction solution is changed to 2 hours, while the other conditions are the same as in Example 2.

[0041] Example 5 This embodiment provides another zinc anode material with porous molecular layer modification and multiple hydrogen bond topological anchoring, the preparation method of which includes: Step S1: Preparation of solid powder product: (1) Dissolve 3.0 mmol of carboxylic acid monomer in a mixed solution of tetrahydrofuran and water, and stir continuously at room temperature for 30 min to obtain a homogeneous carboxylic acid monomer solution C; wherein the mixed solution is obtained by mixing water and tetrahydrofuran at a volume ratio of 0.3:1.

[0042] The structure of the carboxylic acid monomer is as follows: .

[0043] (2) 2.0 mmol of amidine monomer was placed in a mixed solution of tetrahydrofuran and water and stirred continuously at room temperature for 30 min to obtain a homogeneous amidine monomer solution B; wherein the mixed solution was obtained by mixing water and tetrahydrofuran at a volume ratio of 0.3:1.

[0044] The structure of the amidoyl monomer is as follows: .

[0045] (3) Under continuous stirring at room temperature, the amidoyl monomer solution B is slowly added dropwise to the carboxylic acid monomer solution C, and the resulting reaction system is allowed to stand for 7 days.

[0046] (4) The reaction system was slowly filtered at room temperature, and the solid product on the filter paper was washed with tetrahydrofuran. Finally, it was dried in a vacuum drying oven at 60 °C to collect the solid powder product.

[0047] Step S2, zinc sheet surface finishing: Dissolve 5 mg of solid powder uniformly in 1 mL of ethanol to prepare 5 mg mL of the solution. -1 The zinc sheet with a polished surface is immersed in the reaction solution and left to stand for 30 minutes. The zinc sheet is then removed, cleaned, and dried to obtain a zinc anode material modified with a porous molecular layer topologically anchored by multiple hydrogen bonds.

[0048] Example 6 The difference from Example 5 is that only the carboxylic acid monomer is replaced, while the other conditions are the same as in Example 5.

[0049] The structure of the carboxylic acid monomer used is as follows: .

[0050] Comparative Example 1 As a control experiment for the above embodiments, a zinc anode without any surface modification is provided. The difference between this comparative example and the embodiments is that the zinc sheet is directly used for battery assembly and testing after surface polishing.

[0051] To further clarify the electrochemical performance of the porous molecular layer modified zinc anode provided in the embodiments of the present invention, the zinc anodes in Examples 1-6 and Comparative Example 1 were used as anode samples for the assembly of aqueous zinc-ion batteries: the deposition behavior and coulombic efficiency of the zinc anode were tested by assembling Zn|Cu battery structures, and the electrochemical cycle characteristics of the zinc anode were tested by Zn|Zn symmetric batteries. All test batteries used 2M ZnSO4 as electrolyte and GF-D glass fiber membrane as separator.

[0052] Test and Results Analysis By employing acid and base groups to transfer protons, two monomers are made to exist in anionic and cationic forms, respectively. This ionic linkage strengthens the hydrogen bonds between organic monomer molecules, giving the building blocks a directional and regular arrangement, forming a structure on a zinc sheet. Figure 1 The diagram shows a continuous topology network structure with stable connections. For example... Figure 2 The chemical reaction mechanism shown in this invention utilizes the amidine group as a proton acceptor to form cation units and the sulfonic acid group or carboxylic acid group as a proton donor to form anion units. Hydrogen bonding is strengthened through charge-assisted bonding to form a stable topological porous network structure. Based on this, the periodic arrangement of monomers constructs a porous framework material with crystalline properties, such as... Figure 3 As shown, the material exhibits obvious crystal diffraction signals, proving its excellent crystallinity. Crystalline porous network materials offer advantages in rapid ion conduction, ion desolvation processes, and the electrochemical cycling stability of modified electrode materials.

[0053] The transport and movement of ions determine the activity level of the negative electrode reaction. Zinc ion transference number tests were performed on Comparative Example 1 and Examples 1-6, as shown in Table 1. It can be seen that Comparative Example 1 has a lower zinc ion transference number, indicating that the unmodified zinc negative electrode has limited zinc ion transport efficiency and is easily affected by anion migration, leading to interfacial side reactions and dendrite growth. Examples 1-6 all have higher zinc ion transference numbers, indicating that the porous molecular layer topologically anchored by multiple hydrogen bonds can optimize the zinc ion transport path through the topological porous network and promote the zinc ion desolvation process.

[0054] Compared to Example 1, Example 2 exhibits a superior zinc ion transference number, indicating that the fluorine groups in the system of Example 2 can form stronger multiple hydrogen bonds with water molecules, thereby inhibiting the reactivity of water and demonstrating superior zinc ion desolvation capability. Examples 5 and 6 also verify this trend. Example 2 has a higher zinc ion transference number than Example 6, indicating that in this porous molecular layer, sulfonic acid groups can form stronger coordination interactions with zinc ions compared to carboxylic acid groups, thereby reducing the coordination number of zinc ions with water molecules and further lowering the desolvation energy barrier through electrostatic attraction with anions.

[0055] In Examples 2-4, Example 3 had the highest zinc ion migration number, indicating that a porous molecular layer of appropriate thickness can more effectively promote ion transport rate.

[0056] Table 1. Comparison of ion transport numbers between the examples and the comparative examples. The deposition behavior on the zinc anode surface was evaluated using a Zn||Cu half-cell. For example... Figure 4 As shown, Example 3 exhibits a smaller deposition overpotential compared to Comparative Example 1, indicating that the porous molecular layer-modified negative electrode, through its topological porous structure and the anchoring ion-molecule interactions of its periodic polar groups, can significantly enhance zinc ion deposition kinetics. This is achieved at current densities as high as 20 mA cm⁻¹. - ² and has a capacity of 4 mAh cm - Under the test conditions of ², such as Figure 5 As shown, Example 3 exhibited stable cycling for over 360 cycles with a coulombic efficiency exceeding 99%; while Comparative Example 1 only showed significant efficiency fluctuations after 80 cycles. These results indicate that dendrite growth caused by uneven zinc ion deposition in Comparative Example 1, and electrochemical corrosion of zinc metal induced by the enrichment of active water molecules at the zinc anode / electrolyte interface, are important factors limiting battery cycle life and coulombic efficiency.

[0057] In a Zn||Zn symmetric cell, such as Figure 6 As shown, Comparative Example 1 exhibits a significantly shorter cycle life due to the rapid accumulation of dendrites and side reactions. In contrast, the porous molecular layer-modified zinc anode of Example 3 demonstrates better cycle stability. At a current density of 5 mA cm⁻¹... - ², Deposition capacity is 1 mAh cm⁻¹ -Under the given conditions, the symmetric cell of Example 3 could cycle stably for approximately 820 hours, indicating that the porous molecular protective layer can improve zinc utilization and the reversibility of peeling / embedding cycles. Simultaneously, the cycling voltage of Example 3 was significantly lower than that of Comparative Example 1, demonstrating that the topological network provides abundant zinc-loving sites and rapid transport channels for zinc ion migration through multiple hydrogen bonds, thereby significantly accelerating the zinc ion migration rate and promoting zinc ion desolvation and zinc deposition processes. The faster desolvation process not only helps alleviate side reactions initiated by active water molecules at the zinc anode interface but also enhances zinc ion transport kinetics.

[0058] By disassembling the cycled battery and observing the surface of the negative electrode, it can be found that, for example... Figure 7 As shown, Example 3 has a brighter surface than Comparative Example 1, while Comparative Example 1 exhibits irregular black areas. This indicates that the zinc anode modified with molecular layers can maintain a relatively smooth and dense morphology after multiple depositions / strippings, while the surface of Comparative Example 1 shows partial corrosion due to obvious irregular deposition and dendrite growth. The topologically porous molecular layer provides a large number of uniformly distributed zinc-loving sites, so that zinc ions no longer concentrate in a few locally highly active areas, but nucleate more uniformly across the entire interface, thereby promoting more uniform and dense zinc deposition.

[0059] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and various changes or modifications can be made to these embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is defined only by the appended claims.

Claims

1. A method for preparing a zinc negative electrode, characterized in that, Includes the following steps: S1. Under stirring, the amidoyl monomer solution containing amidoyl organic small molecule monomers is added dropwise to the acid monomer solution containing acid group organic small molecule monomers. After static reaction, a porous network material is obtained. Then, after filtration, washing and drying, a solid powder product is obtained. S2. The solid powder product is prepared as a reaction solution, and the surface-polished zinc sheet is immersed in the reaction solution. After cleaning and drying, a zinc anode modified with a porous molecular layer with multiple hydrogen bond topological anchoring is obtained. Wherein: the acidic organic small molecule monomer is selected from one of the following structures: The amidine-based organic small molecule monomer is selected from one of the following structures: ; The acidic organic small molecule monomer is selected from one of the following structures: The amidine-based organic small molecule monomer is selected from one of the following structures: 。 2. The method for preparing the zinc negative electrode according to claim 1, characterized in that, The solvent used for the amidine monomer solution and the acid monomer solution is a mixed solution of tetrahydrofuran and water, which is obtained by mixing water and tetrahydrofuran at a volume ratio of 0.1 to 0.6:

1.

3. The method for preparing the zinc negative electrode according to claim 1, characterized in that, The molar ratio of the sulfonic acid group organic small molecule monomer to the amidoyl organic small molecule monomer is 2:3 to 2:6; and / or, the molar ratio of the carboxylic acid group organic small molecule monomer to the amidoyl organic small molecule monomer is 3:2 to 4:

2.

4. The method for preparing the zinc negative electrode according to claim 1, characterized in that, The settling reaction time is 3-9 days; and / or, in the washing and drying steps, the filtered solid product is washed with tetrahydrofuran and dried in a vacuum drying oven at 50-60 °C.

5. The method for preparing the zinc negative electrode according to claim 1, characterized in that, The solid powder product was uniformly dissolved in ethanol to prepare a concentration of 2-8 mg / mL. -1 The reaction solution; and / or, the zinc sheet is immersed in the reaction solution for 30 min to 2 h.

6. The zinc anode prepared by the method according to any one of claims 1-5.

7. The application of the zinc negative electrode according to claim 6 in an aqueous zinc-ion battery.

8. A zinc-ion battery, characterized in that, It includes an aqueous zinc salt electrolyte and the zinc negative electrode as described in claim 6.

9. The zinc-ion battery according to claim 8, characterized in that, The zinc salt concentration in the aqueous zinc salt electrolyte is 0.5~5 mol / L. -1 .

10. The zinc-ion battery according to claim 8, characterized in that, The zinc salt is selected from at least one of zinc sulfate, zinc trifluoromethanesulfonate, zinc bis(trifluoromethanesulfonate)imide, zinc perchlorate, zinc chloride, zinc nitrate, zinc acetate, zinc fluoride, zinc hexafluoroate, zinc tetrafluoroborate, and zinc gluconate.